Mediation Hub or Active Agent? FAO's Commitment to Rural Welfare During Its First Thirty Years. - De Prospo, Mario (Journal of World History, 2024)
This article provides an overview of the Food and Agriculture Organization's (FAO) efforts to promote rural welfare and development. It discusses the challenges faced by the FAO, such as coordination issues and criticisms of inefficiency. The article also highlights the changing political landscape and demands from developing countries, which led to a rethinking of FAO programs and a greater focus on social justice and the needs of rural populations. The FAO adapted its strategies and approaches to address these demands and became a place of dialogue and collaboration among different actors. Overall, the FAO's role in rural welfare reflects its ability to adapt and respond to changing global dynamics and demands.